Demokrasi Digital dan Ujaran Kebencian: Antara Kebebasan Berekspresi dan Represi Politik: Paradoks Ujaran Kebencian dalam Kasus Dhandy - Rahman, Fathor (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2025)
This study employs a qualitative approach with a descriptive-analytical method to examine the phenomenon of hate speech within the context of cyberdemocracy, particularly in relation to the case of Dandhy Dwi Laksono on the Facebook social media platform. A case study approach is chosen to conduct an in-depth analysis of a specific incident by taking into account the surrounding social, political, and media contexts. This method enables the researcher to gain a comprehensive understanding of the complex social dynamics and digital interactions involved, including public responses to the hate speech in question. The study aims to explore the process of public opinion formation, the mechanisms of production and distribution of hate speech in digital spaces, and the role of social media as a contested arena for discourse and freedom of expression within the framework of Indonesia’s digital democracy. Thus, this research not only examines the textual aspects of hate speech but also analyzes the accompanying socio-political implications, as well as the dynamics of power and resistance within an ever-evolving cyberspace.